Exchange rates and competition for FDI - Yuqing Xing; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper analyses the role of exchange rates in the competition for FDI. Based on the assumption that two countries compete for FDI from the same source country, the paper shows explicitly that the relative FDI of one country is determined by the relative real exchange rate between its currency and that of the source country. The theoretical result suggests that, if the currency of one FDI recipient country appreciates against the source country more than that of its rival, its FDI inflows will decrease while the competing country's FDI will increase. Using data on Japan's FDI in nine Asian manufacturing sectors from 1981 to 2002, the paper also examines the theoretical conclusion in the context of the competition between China and ASEAN-4 (Indonesia, Malaysia, the Philippines and Thailand). Empirical results show that the relative exchange rate is a statistically significant factor determining the relative inflows of Japanese FDI for manufacturing as a whole and for such sub-sectors as textiles, food, electronics, transportation equipment, and others. Exchange rate polices of the ASEAN-4 countries played a critical role in dynamically reshaping the geographic distribution of Japan's FDI in Asia. – FDI ; exchange rate ; China ; ASEAN-4
Keywords: F14; F23; F31; 330; Direktinvestition; Internationaler Wettbewerb; Wechselkurs; China; ASEAN-Staaten; Indonesien; Malaysia; Philippinen; Thailand